2014
DOI: 10.15419/ajhs.v2i1.414
|View full text |Cite
|
Sign up to set email alerts
|

Can Controlled Vestibular Stimulation Delay Brain Aging?

Abstract: Aging is believed to be a first-order risk factor for most neurodegenerative disorders. Brain changes do not occur to the same extent in all brain regions.7 Men and women may also differ with frontal and temporal lobes most affected in men compared with the hippocampus and parietal lobes in women. The neurotransmitters most often discussed with regard to ageing are dopamine, serotonin and acetyl-choline. Vestibular stimulation modulates the neuro-transmitters which are involved in brain aging and delay aging. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…[ 23 ] Stress activates hypothalamo-pituitary-adrenal (HPA) axis, leading to various endocrine disorders such as high cortisol and low sex steroid levels, which antagonize the actions of insulin. [ 24 ] Controlled vestibular stimulation inhibits HPA axis,[ 25 ] which further supports the role of vestibular stimulation in the regulation of diabetes. Although these are only association, it would be necessary to explore such associations for further therapeutic development.…”
Section: Methodsmentioning
confidence: 73%
“…[ 23 ] Stress activates hypothalamo-pituitary-adrenal (HPA) axis, leading to various endocrine disorders such as high cortisol and low sex steroid levels, which antagonize the actions of insulin. [ 24 ] Controlled vestibular stimulation inhibits HPA axis,[ 25 ] which further supports the role of vestibular stimulation in the regulation of diabetes. Although these are only association, it would be necessary to explore such associations for further therapeutic development.…”
Section: Methodsmentioning
confidence: 73%
“…Previous studiesobserved that stimulation of the vestibular apparatus increases acetylcholine release from rat hippocampus during anxiety and depression. It is also known to enhance memory by activating through a cholinergic pathway of the hippocampus (Horii et al, 1994;Sailesh et al, 2014b). However, the literature evidence for the bene icial effect of CVS on the prevention of Parkinson's Disease induced by rotenone is undetermined.…”
Section: Introductionmentioning
confidence: 99%
“…A thorough review of literature revealed that vestibular stimulation inhibits both HPA axis and SAM axis and decreases cortisol level and heart rate and blood pressure within normal limits and brings to stressless condition. [6] Recent studies show that several audiovestibular pathologies in the paediatric population may be immune-mediated. [7] The purpose of this article is to review research reports related to vestibular stimulation and its role on balance of stress and immunity, with the intent of clarifying the present knowledge base in this area, and suggesting future research needs.…”
Section: Introductionmentioning
confidence: 99%